Fog Formation in Cold Season in Ji’nan, China: Case Analyses with Application of HYSPLIT Model - Xinfeng Wang; Jianmin Chen (Advances in Meteorology)
Fog events almost happened every year in cold season in North China Plain. In this study, hybrid single-particle Lagrangian integrated trajectory (HYSPLIT) model was applied to analyze the formation of four fog events occurring in Ji’nan, China, during the period from March 2012 to February 2014. Three types of fog have been distinguished, including radiation fog, advection fog, and frontal fog. When fog events happened, the average surface temperature ranged from near zero to 10°C and the relative humidity was around 90%. Fog events often happened immediately after haze episodes (i.e., fog-haze) and sometimes after light rain. Back trajectory analyses show that the air masses during the fog events mostly came from the local Shandong areas and moved in very slow speed (4–24 km h−1). During the fog events, the humidity along the air trajectories always gradually increased to saturation. The mixed layer depth was small, generally below 400 m at noon and around 100 m at midnight. However, the air temperature exhibited complex variations—sometimes decreased and sometimes kept stable or even increased.